Clinical differentiation between ovarian granulosa cell tumor and ovarian cancer: a review - Chyćko, Małgorzata; Czarnota, Julia; Cichoń, Katarzyna; Lasota, Nina; Lambach, Maciej; Younes, Martyna; Demidowicz, Gabriela; Wiśniewski, Wojciech; Kowalczyk, Klaudia; Trąbka, Natalia (Journal of Education, Health and Sport, 2023)
Differentiation of granulosa cell tumor and ovarian cancer doesn’t seem to cause much trouble in everyday clinical work. Despite quite easy distinction, within the researches discussed within this review, findings were suggesting less obvious results. There was a huge urge to take into consideration immunohistochemical differentiation. Common symptoms of many gynecological tumors are very similar, studies investigated that GCT and ovarian cancer frequently overlap. Symptoms, method of treatment and prevalence rate (at some point) are often shared between these neoplasms. Fortunately, great distinction was provided by immunohistochemical findings.